ANALISIS PRAANGGAPAN DALAM SERIAL ANIMASI PADA ZAMAN DAHULU - Rahuel, Roby; Sanulita, Henny; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractPresupposition is something that the speaker assumes as an event before producing speech. Presupposition can help to interpreted a massage that the speaker wants to convey to be directed. Presupposition can be known through the speech in the animation. Animation is a kind of film that is very familiar with human life. The purpose of the study is the description a kind of the presupposition, the entailment contained in the animation series Pada Zaman Dahulu and learning implementation plans. The method that used in this research is descriptive method with qualitative research. The sources of data in this research is video documentary animation Pada Zaman Dahulu, which the form of the data is text speech figures in animation series Pada Zaman Dahulu containing presupposition that has been transcribed. The technique that used in this research is documentary study technique, while the tools that used in this research are laptop and data card. Based in the data analisys, the results of this research as follows: (1) a types presupposition that include existential presupposition there are twenty-one data, factive presupposition contained nineteen data, non-factive presupposition contained ten data, structural presupposition contained niniteen data, and lexical presupposition contained nine data, (2) entailment contained fourteen data, and (3) learning implementation of animation Pada Zaman Dahalu can be learning material in the curriculum education 2013.Â Keywords: Presupposition, Entailment, Pada Zaman Dahulu